Bioenergetics and mitochondrial dynamics in cancer cells and neurons - Quinn, Stephen (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2012)
Mitochondria in mammalian cells exist as a highly dynamic and interconnected reticulum. This reticular ultrastructure is defined by the opposing forces of fission and fusion, mainly mediated by a group of large GTPases collectively known as mitodynamins. The regulation of fission and fusion is poorly understood but it is thought that bioenergetics and dynamics engage in a bi-directional crosstalk, such that disturbing one will have deleterious effects on the other. The pathophysiological hallmarks of mitochondrial dysfunction are evident both in cancer and neurodegeneration, implicating a role for disturbed mitochondrial dynamics. This study explores the effects of bioenergetic modulation on mitochondrial fusion rates in human cervical carcinoma HeLa cells and rat primary cortical neurons.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin